Aluminium complexes of B- and N-based hydrides: Synthesis, structures and hydrogen storage properties. (14th September 2016) - Dovgaliuk, I.; Filinchuk, Y.
Abstract: The storage of hydrogen in a solid state is one of the main challenges for stationary and mobile applications. Light metal hydrides have attracted significant attention as potential candidates for energy storage. Remarkably, Al-containing hydrides, namely AlH3 and M(AlH4 ) n, are among the most fascinating classes of materials, able to cycle up to 5.5 wt% of hydrogen at moderate temperatures. This review covers the recent research on the families of Al-based complex hydrides involving other light elements such as B and N. They were classified according to the charge of the Al-based complexes, as anionic, molecular, cationic or "autoionized" where Al is centering both the cation and the anion. The factors influencing the stability and the hydrogen purity of the series of anionic aluminium amides M[Al(NH2 )4 ] n, borohydrides M[Al(BH4 )4 ] and amidoboranes M[Al(NH2 BH3 )4 ], as well as molecular [Al(L)(BH4 )3 ] (L = molecular ligands) and cation [Al(NH3 )6 ] 3+ -based complexes are discussed. In particular, the ability of the strong Lewis acid Al 3+ to coordinate both the initial hydrogenated species as well as their dehydrogenation products makes it a good template for chemical transformations involving light chemical and complex hydrides. Graphical abstract: Highlights: Al complexes with B- and N-based hydrides show good capacity for hydrogen storage. Al 3+ is a Lewis acid, coordinating the initial light hydrides and the dehydrogenation products, favouring the reversibility. The factors influencing the stability and hydrogen purity are determined.